Syphilis of the fetus - G. I. Mavlyutova; L. A. Yusupovа; Z. Sh. Garaeva; E. I. Yunusovа; M. F. Sharkhemullin; V. A. Lobastov; M. I. Kotov (Лечащий Врач)
The article reflects the main aspects of the current clinical course of congenital syphilitic infection, provides detailed information about the features of intrauterine fetal pale Treponema, and also offers our own clinical observation of the epidemiological case of congenital syphilis (ECCS). Tactics of interaction between obstetrician-gynecologists and dermatologists for the prevention of congenital syphilis.